Community development - Mavis Arthur (AOSIS, 1981)
HEALTH EDUCATION - THE NEED TO MAKE IT WORK It is increasingly apparent that the major health problems in the world today - ranging from malnutrition and communicable diseases; many forms of mental ill-health and cardiac conditions; accidents and alcoholism, are primarily attributable to unsatisfactory living conditions, lack of knowledge and harmful practices on the part of individuals, families and communities. Advances in the field of science and technology can do no more towards the promotion of the health of the population unless it is accompanied by fundamental changes in the way of life and behaviour patterns of the people themselves.